IRSp53 mediates podosome formation via VASP in NIH-Src cells. - Tsukasa Oikawa (Public Library of Science (PLoS), 2013)
Podosomes are cellular "feet," characterized by F-actin-rich membrane protrusions, which drive cell migration and invasion into the extracellular matrix. Small GTPases that regulate the actin cytoskeleton, such as Cdc42 and Rac are central regulators of podosome formation. The adaptor protein IRSp53 contains an I-BAR domain that deforms membranes into protrusions and binds to Rac, a CRIB motif that interacts with Cdc42, an SH3 domain that binds to many actin cytoskeletal regulators with proline-rich peptides including VASP, and the C-terminal variable region by splicing. However, the role of IRSp53 and VASP in podosome formation had been unclear. Here we found that the knockdown of IRSp53 by RNAi attenuates podosome formation and migration in Src-transformed NIH3T3 (NIH-Src) cells. Importantly, the differences in the IRSp53 C-terminal splicing isoforms did not affect podosome formation. Overexpression of IRSp53 deletion mutants suggested the importance of linking small GTPases to SH3 binding partners. Interestingly, VASP physically interacted with IRSp53 in NIH-Src cells and was essential for podosome formation. These data highlight the role of IRSp53 as a linker of small GTPases to VASP for podosome formation.